Pengaruh Komisi Marketing Agent dan Tenaga Penjual Terhadap Target Penjualan yang Dimediasi oleh Citra Perusahaan: Studi pada WOM Finance Cabang Serang - Yolanda Ryda Megawati Br Sitorus Sitorus; Budi Haryono; Eka Desy Purnama (CV. Ulil Albab Corp, 2024)
This research aims to analyze the influence of marketing agent commissions and sales personnel on sales targets, mediated by the company's image at WOM Finance Branch Serang. The objects of this study include sales targets of marketing agents, company image, marketing agent commissions, and sales personnel at PT WOM Finance Branch Serang. The subjects of the research are the company and the marketing agents of PT WOM Finance. The population data is derived from the number of marketing agents who contributed to sales from January to December 2023. Using the sampling method according to Hair et al. (1998), a sample of 100 respondents was obtained. The research results indicate that Marketing agent commissions have a significant positive impact on sales targets. Sales personnel also have a significant positive impact on sales targets. Marketing agent commissions significantly positively affect the company's image. Sales personnel significantly positively affect the company's image. The company's image significantly positively impacts sales targets. The company's image significantly mediates the relationship between marketing agent commissions and sales targets. The company's image also significantly mediates the relationship between sales personnel and sales targets. This study emphasizes the importance of the company's image as a mediating factor in the relationship between marketing agent commissions and sales personnel on achieving sales targets at PT WOM Finance Branch Serang.